The Effects of the Multimedia "English Discoveries" Program on the Learning of Five Different Language Skills by High School Students - Jorge Benavides (Asociación Colombiana de Profesores de Ingles, 2006)
This study determines the effects of the application of multimedia technology -computer-assisted language learning (CALL) in the development of five language skills using "English Discoveries". It shows that the effects of multimedia materials for language learning are not necessarily better as a whole, but different from those obtained in traditional classroom work. Only two of the five variables showed significant differences in favor of the use of multimedia: pronunciation and oral production. However, grammar showed opposite results. The teachers' and students' reactions suggest the need to adapt their roles to the new context in the future use of CALL and multimedia. The high level of acceptance of this type of materials by the students shows the need for more research and better adaptation of activities to the new context.